2010
DOI: 10.3402/fnr.v54i0.2149
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fibre amount, energy level and viscosity of beverages containing oat fibre supplement on perceived satiety

Abstract: BackgroundSoluble fibre has been proposed to suppress appetite-related perceptions and it could thus contribute favourably to the regulation of energy intake and the increasing obesity problem.ObjectiveTo investigate the effect of an oat ingredient rich in β-glucan on perceived satiety at different dietary fibre (DF) concentrations, energy levels and viscosity levels.DesignA total of 29 healthy volunteers, age 19–39, mean BMI 23.2 kg/m2 participated in this study. Measurement of subjective perceptions (satiety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 21 publications
2
49
0
1
Order By: Relevance
“…Thus, vagal nerve stimulation from other regions of the digestive tract, such as stomach and small intestine, are more likely contributors to modulating diet intake, especially when barley b-glucan can increase digesta viscosity in the upper gut (Brockman et al 2012) and tends to slow the rate of gastric emptying (Belobrajdic et al 2015). These observations align with clinical studies which showed that oat b-glucan increased perceptions of satiety during the postprandial period Juvonen et al 2009;Lyly et al 2010;Pentikainen et al 2014;Rebello et al 2013Rebello et al , 2014 and modulated the secretion of satiety hormones in the small intestine, including cholecystokinin, ghrelin and peptide YY Vitaglione et al 2009). Therefore, b-glucan fermentation in the large bowel is unlikely to contribute to reduced energy intake and body weight.…”
Section: Discussionsupporting
confidence: 81%
“…Thus, vagal nerve stimulation from other regions of the digestive tract, such as stomach and small intestine, are more likely contributors to modulating diet intake, especially when barley b-glucan can increase digesta viscosity in the upper gut (Brockman et al 2012) and tends to slow the rate of gastric emptying (Belobrajdic et al 2015). These observations align with clinical studies which showed that oat b-glucan increased perceptions of satiety during the postprandial period Juvonen et al 2009;Lyly et al 2010;Pentikainen et al 2014;Rebello et al 2013Rebello et al , 2014 and modulated the secretion of satiety hormones in the small intestine, including cholecystokinin, ghrelin and peptide YY Vitaglione et al 2009). Therefore, b-glucan fermentation in the large bowel is unlikely to contribute to reduced energy intake and body weight.…”
Section: Discussionsupporting
confidence: 81%
“…The incorporation of oat β-glucans (from 2.5 g to 5 g) into beverages with different energy contents, showed a higher perception of satiety compared to control food, but a doseresponse relationship was not observed. Moreover, the oat had a high viscosity which produced the increased perception of satiety [74]. In the same way Beck et al, showed that a lower dose of oat β-glucan (2.2 g) was able to increase subjective satiety while an higher dose of 5 g of β-glucans reduced energy intake by more than 400 kJ in the subsequent meal [75].…”
Section: Most Promising Functional Foods To Increase Satiety Accordinmentioning
confidence: 87%
“…In beverages, however, Wbre could be used to boost their satiating capacity closer to the level of solid or semisolid foods, or even above it, which was the case in the study by Lyly and their team [46], when compared to white wheat bread. This could oVer an interesting possibility for the beverage industry to produce functional beverages with improved eVect of liquid calories on satiety [46]. Naumann et al [51] showed that when incorporated into a fruit drink, -glucan lowers serum concentrations of total and LDL cholesterol.…”
Section: Satietymentioning
confidence: 96%
“…Oat -glucan has been suggested to be crucial for their eVect on satiety-related attributes [64]. Burton-Freeman [10] and Howarth et al [30] discuss several possible mechanisms behind the inXuence of soluble viscous Wbres on food intake regulation: the slower gastric emptying time because of increased viscosity of the chyme in the gut as well as longer small intestine passage time and the absorption rate of nutrients, both of which are believed to increase satiety by enhancing satiety-mediating signals to the central nervous system [46]. Howarth et al [30] suggested direct eVect of dietary Wbre on energy intake is the decreased absorption of macronutrients because of the physical barrier formed by dietary Wbre.…”
Section: Satietymentioning
confidence: 98%